ANALYSING THE ROLE OF HR ANALYTICS IN STRATEGIC DECISION MAKING - Thomas, Lilly; Leo, Rekha Susan; Javeria, Nida; Taj, Nayara (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Analytics for human resources (HR) have become a vital tool for contemporary organizational management, allowing for data-driven choices that are in line with strategic goals. The incorporation of HR analytics into strategic decision-making procedures is examined in this abstract, with a focus on how it might significantly improve organizational performance. The study looks at how insights into workforce dynamics, talent management, employee engagement, and productivity from HR analytics help make well-informed decisions. HR specialists may enhance resource allocation, reduce risks, and identify trends by utilizing predictive analytics, which will provide their company a competitive edge. The abstract also addresses the difficulties in implementing HR analytics, such as the requirement for qualified staff, data privacy issues, and integrating analytics with current HR systems. The study presents real-world examples of how businesses effectively applied HR analytics to achieve strategic goals, highlighting the practical advantages of data-driven HR procedures. The results emphasize how crucial it is for HR departments to develop a data-centric culture in order to properly utilize HR analytics in strategic decision-making. These abstract lays the groundwork for an in-depth examination of how HR analytics is changing the strategic environment and provides a road map for businesses looking to improve their decision-making processes with cutting-edge data.